ICLS 2021 Best Design Paper Award - Kyza, Eleni A. (My University, 2026)
Agesilaou, A. & Kyza, E. A. (2021, June 7-11). Empowering students to be data literate: The design and implementation of a learning environment to foster critical data literacy. Presented at the 1st ISLS Annual Meeting “Reflecting the Past and Embracing the Future”, Bochum, Germany. Link to award announcement: https://2021.isls.org/wp-content/uploads/2021/06/ISLS-2021-Awards-v2.pdf
Keywords: Education